The Effect of Corporate Ownership and Earning Management on Tax Avoidance with Corporate Governance as a Moderation - Bayu Bagus SETIANUGRAHA; Siti NURYANAH (Communications of International Proceedings, 2020)
This research aims to analyze the effect of corporate ownership, earnings management, and corporate governance on tax avoidance. This study also examines moderating effects of corporate governance on the impact of corporate ownership, and earnings management on tax avoidance. Sample used are 68 manufacturing companies listed in Indonesia Stock Exchange with total observation of 204 firms. The results of this research are: first, corporate ownership has no effect on tax avoidance. Second, earnings management have a positive effect on tax avoidance. Third, good corporate governance practice have a negative effect on tax avoidance. Fourth, there is a moderating effect of good corporate governance on the positive effect of earnings management on tax avoidance. And last, there is no moderating effect of good corporate governance on the positive effect of corporate ownership on tax avoidance.
Keywords: Corporate Ownership; Earning Management; Corporate Governance; Tax Avoidance